Moso bamboo (Phyllostachys edulis (Carrière) J. Houzeau) invasion affects soil microbial communities in adjacent planted forests in the Lijiang River basin, China - Sun, Hongping; Hu, Wenyu; Dai, Yuxin; Ai, Lin; Wu, Min; Hu, Jing; Zuo, Zhen; Li, Mengyao; Yang, Hao; Ma, Jiangming (Frontiers in Microbiology, 2023)
Moso bamboo (Phyllostachys edulis (Carr.) J. Houz.), the most widely distributed bamboo species in southern China’s karst areas, can easily invade adjacent communities due to its clonal reproduction. However, there is little information on the effects of its establishment and expansion to adjacent forest soil communities, particularly for planted forests. We investigated the relationships between soil properties and microbial community during bamboo invasion under different slope directions and positions for the three typical stand types in the Lijiang River Basin. This study aimed to explore the effects of key environmental factors on soil microbial composition, diversity, and abundance. The results showed that five microorganisms (Acidobacteria, Gammaproteobacteria, Alphaproteobacteria, Betaproteobacteria and Actinobacteria) dominate the invasion of bamboo at the species level, and were most affected by slope position. On the bottom and middle slopes, the microbial diversity of the shady slopes was less than that of the sunny slopes. The pH, organic matter (OM) and total phosphorus (TP) were the key soil environmental factors; most microorganisms showed a positive relationship with pH and a negative relationship with OM and TP. Slope position significantly affected OM, calcium (Ca), total nitrogen (TN), available phosphorus (AP), and hydrolyzed nitrogen (HN), pH, and also significantly affected microbial abundance and composition. The slope direction significantly affected the TP, magnesium (Mg). The structural equations also indicated that slope position had an effect on microbial composition, abundance, and diversity. Slope position was negatively correlated with pH (r=-0.333, P=0.034) and positively correlated with OM (r=0.728, P<0.001), TN (r=0.538, P<0.001) and Ca (r=0.672, P<0.001) directly; pH was positively correlated with microbial composition (r=0.634, P<0.001), abundance (r=0.553, P<0.001) and diversity (r=0.412, P=0.002), TN was positively correlated with microbial composition (r=0.220, P=0.014) and abundance (r=0.206, P=0.013), and Ca was negatively correlated with composition (r=-0.358, P=0.003) and abundance (r=-0.317, P=0.003). Slope position also can influence microbial composition (r=0.452, P<0.001) directly. In addition, slope direction had an indirect effect on microbial diversity through TN. Therefore, we proposed that the different variations in microbial community during bamboo invasion could be related to the influence of invasion on the soil properties at different invasion stages.